2017
DOI: 10.4103/0972-0707.209066
|View full text |Cite
|
Sign up to set email alerts
|

Apical extrusion of debris in four different endodontic instrumentation systems: A meta-analysis

Abstract: Background:All endodontic instrumentation systems tested so far, promote apical extrusion of debris, which is one of the main causes of postoperative pain, flare ups, and delayed healing.Objectives:Of this meta-analysis was to collect and analyze in vitro studies quantifying apically extruded debris while using Hand ProTaper (manual), ProTaper Universal (rotary), Wave One (reciprocating), and self-adjusting file (SAF; vibratory) endodontic instrumentation systems and to determine methods which produced lesser … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 35 publications
1
16
0
Order By: Relevance
“…In the present study, evaluation of the apical extrusion of debris produced by continuous rotary-file systems versus single-file reciprocating system demonstrated that all instruments created apical debris extrusion, in agreement with the previous studies. 1 5 10 29 31 32 33 Dincer at al reported that continuous rotary systems extruded more debris than reciprocating systems (dried extruded debris) at the WL. 31 In addition, Karataş et al specified that WOG system produced less debris than the continuous rotation systems such as the ProTaper Gold and ProTaper Universal systems.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, evaluation of the apical extrusion of debris produced by continuous rotary-file systems versus single-file reciprocating system demonstrated that all instruments created apical debris extrusion, in agreement with the previous studies. 1 5 10 29 31 32 33 Dincer at al reported that continuous rotary systems extruded more debris than reciprocating systems (dried extruded debris) at the WL. 31 In addition, Karataş et al specified that WOG system produced less debris than the continuous rotation systems such as the ProTaper Gold and ProTaper Universal systems.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that all canal preparation techniques are associated with wide-ranging variability in debris extrusion depending on the mechanical systems used. [ 12 13 14 15 ] This could be attributed to differences in the cross-section, cutting-edge design, taper, tip type, configuration, concept of use, flexibility, alloy type, number of files used, kinematics, or cutting efficacy. [ 16 ] The alterations in these properties may be the determinants responsible for higher pain scores of Group A and Group B when compared to Group C.…”
Section: Discussionmentioning
confidence: 99%
“…In the process of root canal preparation, irritants such as infected debris can be squeezed into the periapical tissue to induce acute inflammatory reaction. So far, all the instruments and techniques of root canal preparation are related to a certain degree of fragment extrusion [5,6]. Glide path preparation, establishment of apical patency and endodontic status are important factors that affect and reduce the incidence of the post-treatment pain [3,[7][8][9].…”
Section: Introductionmentioning
confidence: 99%